Leveraging the Potential of Sorghum as a Healthy Food and Resilient Crop in the South African Food System - Pereira, Laura M.; Hawkes, Corinna (Frontiers in Sustainable Food Systems, 2022)
An erosion of indigenous and traditional foods in the Global South has dramatically changed the global food system in the last 50 years. Reinvigorating these crops and the agro-biodiversity that they represent could provide benefits for healthier and more sustainable food systems. In South Africa, it has been proposed that studying indigenous plants more extensively and focussing on innovation to include them as mainstream foods on people's plates could improve food and nutrition security. With this background, this paper aims to contribute to addressing this challenge by researching sorghum (Sorghum bicolor) to identify the opportunities for innovating around sorghum as a healthy food and resilient crop. The paper traces sorghum through various encounters across the South African food system. The results point at clear areas where policy interventions could bolster the sorghum value chain. These include zero-rating VAT on sorghum products, investing more extensively in research and marketing across diverse stakeholders, raising awareness about the health benefits of sorghum and using public procurement as a way of instigating a market for novel sorghum products. The outcomes of a successful sorghum innovation programme could improve smallholder farmers' livelihoods, make a healthy food more accessible to South Africans and develop a local market for innovative products that utilize a crop that is resilient to projected climatic changes.